The Influence of Financial Literacy on Financial Inclusion: Social Capital as Mediating Variable - Gracia F. Goenadi; Werner Ria Murhadi; Endang Ernawati (Media Ekonomi dan Manajemen, 2022)
This study aims to examine how financial literacy affects financial inclusion through social capital mediation. This study uses 150 respondents who have experience, in the investment field in the Indonesian capital market. The independent variable in this study is financial literacy, using four dimensions: skill, behavior, knowledge, and attitude. The mediating variable is social capital using four dimensions (i.e., trust, bonding & bridging, and collective action). At the same time, the dependent variable in this study is financial inclusion, which has four dimensions (i.e., access, quality, usage, and welfare). The result of this research is that social capital has a significant positive effect on financial literacy and financial inclusion, but in this study, social capital has a partial mediating effect. The higher a person's financial literacy, the higher the social capital that person has. The higher a person's financial literacy, the higher the financial inclusion that person has. Our study result states that the higher a person’s financial literacy, the higher the person’s social capital. Besides, the higher a person’s financial literacy, the higher the financial inclusion.